Four new varieties of the family Araceae from Bangladesh (Bangladesh Journal of Plant Taxonomy, 2019)
Four new varieties belonging to four species and three genera of the family Araceae are being described and illustrated from Bangladesh. The new varieties are: Colocasia fallax Schott var. purpurea H. Ara & M.A. Hassan, Colocasia oresbia A. Hay var. stolonifera H. Ara & M.A. Hassan, Rhaphidophora calophyllum Schott var. violaceus H. Ara & M.A. Hassan and Typhonium trilobatum (L.) Schott var. fulvus H. Ara & M.A. Hassan. The morphological diagnostic characters of each new variety and comparison with its closest one are provided. Detailed taxonomic description along with other relevant information are provided for easy recognition of the new aroid taxa.